The Effect of Teacher Social Support on Student Achievement Motivation - Fanggidae, Yenssy Marvilen; Radja, Markus Dimu (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2020)
The purpose of this research is to investigate the influence of teachers' social support on the motivation of achievement students of class XI language department at SMA Negeri 5 Kupang City. The research method used is quantitative, with a simple linear regression data analysis technique. The number of respondents was 35 students, and the sampling technique used was random sampling. The results showed that there was a positive and significant influence on student achievement motivation (Sig. 0.000 < 0.05). While the effective contribution of the teacher's social support to achievement motivation was 58.8%, and the remaining 41.2% was influenced by other variables not included in this study.